AN ANALYSIS OF THE RESULTS OF THE 33RD NU CONGRESS 2015 ON THE PROTECTION OF INDONESIAN MIGRANT WORKERS AND MARRIAGE REGISTRATION FOR MUSLIM MIGRANT WORKERS ABROAD. - Huda, Miftahul; Hidayati, Tri Wahyu (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Indonesian citizens who need marriage registration services abroad do not always get the best service from the Indonesian Representative Office abroad. With this issue, NU provided recommendations in the 33rd NU Mu'tamar to strengthen legal protection for Indonesian workers abroad. This research was conducted to answer questions related to the context in which NU formulated the protection of Indonesian migrant workers and marriage registration for Muslim migrant workers abroad. This research uses normative research with a statutory approach and conceptual approach, so this research is a type of library research. From the results of the 33rd NU Batsul Masail decision on the protection of migrant workers and marriage registration for Muslim migrant workers abroad using the approach of the Fikih rule Qawaid al-Ahkam fi Mashalih al-Anam, where this rule emphasises that on Maslahah mursalah. So it is required for the legislative body to provide more benefits, especially in relation to services for foreign migrant workers who want to register their marriage. This is seen from Law No. 39 of 2004 that has not fully regulated the protection in detail, which results in many violations that occur against migrant workers. Starting from the determination process through TKI service bureaus to placement in the workplace. In addition, Law No. 39 of 2004 does not include matters relating to marriage for overseas workers so that it raises new problems related to the protection of migrant workers, one of which is the problem of marriage registration. Judging from the urgency of marriage registration, it is very necessary to add regulations relating to this matter to Law No. 39 of 2004. With the inclusion of marriage issues in Law No.39 of 2004.